Macro-anatomical investigations on the hedgehog skeleton (Erinaceus europaeus) I- ossa membri thoracici - Özkan, Zait Ender (My University, 2004)
Three adult male hedgehogs (Erinaceus europaeus) were used to investigate the bones of the thoracic limb. It was observed that the area of the fossa supraspinata (48%) was slightly larger than that of the fossa infraspinata (46%). Foramen supracondylare and foramen supratrochleare were absent but in one hedgehog while there was a foramen supratrochleare in the right humerus, there was no such foramen in the left humerus. The tuberositas deltoidea was not developed well but the tuberculum majus and tuberculum minus, crista tuberculi minoris, crista supracondylaris lateralis, epicondylus lateralis and epicondylus medialis were prominent. A spatium interosseum antebrachii was present. The olecranon was large and there was a deep fossa on the medial surface of the olecranon. Three proximal and 4 distal carpal and 5 metacarpal bones were determined.
Keywords: Bones of the thoracic limb; Erinaceus europaeus; Hedgehog